2021
DOI: 10.1161/atvbaha.121.315903
|View full text |Cite
|
Sign up to set email alerts
|

Association of Differential Leukocyte Count With Incident Abdominal Aortic Aneurysm Over 22.5 Years: The ARIC Study

Abstract: Objective: Leukocytes contribute to the development of abdominal aortic aneurysm (AAA). We evaluated whether associations of differential leukocyte counts with AAA persist after accounting for traditional risk factors of AAA. Approach and Results: Among 11 217 adults from the Atherosclerosis Risk in Communities Study, we evaluated associations of differential leukocyte counts at baseline (1987–1989) with incident AAAs over a median follow-up of 22.5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Among inflammatory cells, neutrophils are recruited to the aortic wall at early stage of AAA formation 8 . A prospective cohort study showed a strong positive association between neutrophil count and AAA development, independent of other traditional risk factors such as smoking, obesity, and atherosclerosis 9 . Limiting neutrophil recruitment to the arterial wall significantly reduced the incidence of elastase-perfusion AAA 10 , and inhibition of neutrophils using anti-neutrophil antibodies can be also effective in limiting the progression of experimental AAA 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Among inflammatory cells, neutrophils are recruited to the aortic wall at early stage of AAA formation 8 . A prospective cohort study showed a strong positive association between neutrophil count and AAA development, independent of other traditional risk factors such as smoking, obesity, and atherosclerosis 9 . Limiting neutrophil recruitment to the arterial wall significantly reduced the incidence of elastase-perfusion AAA 10 , and inhibition of neutrophils using anti-neutrophil antibodies can be also effective in limiting the progression of experimental AAA 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In the landmark ARIC study (Atherosclerosis Risk in Communities) of >10 000 diverse participants from 3 communities, >300 individuals developed AAA over a median follow-up of ≈23 years. 2,3 Among the risk factors for incident AAAs included elevated plasma total cholesterol and low-density lipoprotein cholesterol (LDL-C) concentrations. 2 Despite strong epidemiological evidence linking LDL-C to AAAs, connecting pharmacological LDL-C lowering with the prevention of AAA growth and rupture has remained elusive.…”
mentioning
confidence: 99%
“…2,3 Among the risk factors for incident AAAs included elevated plasma total cholesterol and low-density lipoprotein cholesterol (LDL-C) concentrations. 2 Despite strong epidemiological evidence linking LDL-C to AAAs, connecting pharmacological LDL-C lowering with the prevention of AAA growth and rupture has remained elusive. Several observational studies have suggested associations between statin use and lower rates of AAA growth and rupture, 4–7 but findings have not been consistent.…”
mentioning
confidence: 99%